Applications of capillary electrophoresis in the fields of environmental, pharmaceutical, clinical, and food analysis (2019–2021). Issue 11 (15th April 2022) - Wang, Mengyao; Gong, Qian; Liu, Wenfang; Tan, Songwen; Xiao, Jian; Chen, Chuanpin
Abstract : So far, the potential of capillary electrophoresis in the application fields has been increasingly excavated due to the advantages of simple operation, short analysis time, high‐resolution, less sample consumption, and low cost. This review examines the implementations and advancements of capillary electrophoresis in different application fields (environmental, pharmaceutical, clinical, and food analysis) covering the literature from 2019 to 2021. In addition, ultrasmall sample injection volume (nanoliter range) and short optical path lead to relatively low concentration sensitivity of the most frequently used ultraviolet‐absorption spectrophotometric detection, so the pretreatment technology being developed has been gradually utilized to overcome this problem. Despite the review being focused on the development of capillary electrophoresis in the fields of environmental, pharmaceutical, clinical, and food analysis, the new sample pretreatment techniques of microextraction and enrichment fit excellently to capillary electrophoresis in recent three years are also described briefly.